The impact of ultra-processed foods on obesity risk: A comprehensive bibliometric analysis - Richard Osei Agjei; Oluwafemi Samson Balogun; Sunday Adewale Olaleye; Prince Owusu Adoma; Michael Afari-Baidoo; Frank Adusei-Mensah (Clinical Nutrition Open Science)
S U M M A R Y: This study aims to analyze the research landscape pertaining to the impact of ultra-processed foods and their potential association with the risk of obesity. To achieve this objective, a comprehensive bibliometric analysis of the relevant literature published between 2013 and 2022 was conducted. The study primarily examined the prevailing research patterns, scholarly output, and thematic emphasis within scientific literature pertaining to processed foods and its association with the risk of obesity. A bibliometric methodology was utilized to conduct a comprehensive analysis of the data to obtain a thorough understanding of the patterns, thematic emphasis, and scholarly output pertaining to ultra-processed foods (UPFs) and its association with the risk of obesity. The findings derived from this bibliometric research demonstrate a dual contribution to the existing corpus of knowledge. This analysis encompasses several aspects such as current areas of focus, trends in vaccine development, and prospective avenues for future research. The research on ultra-processed foods (UPFs) and its association with obesity has been widely acknowledged and extensively explored, considering the findings reported in this study. The results of this study present potential avenues for further investigation in the realm of research collaboration among governmental/non-governmental organizations and scholars. Additionally, there is a need to broaden the scope of inquiry to explore the connections between ultra-processed foods (UPFs) and additional health-related consequences, such as diabetes and malnutrition.